2016
DOI: 10.1007/s00039-016-0374-7
|View full text |Cite
|
Sign up to set email alerts
|

Counting curves in hyperbolic surfaces

Abstract: Abstract. Let Σ be a hyperbolic surface. We study the set of curves on Σ of a given type, i.e. in the mapping class group orbit of some fixed but otherwise arbitrary γ0. For example, in the particular case that Σ is a once-punctured torus, we prove that the cardinality of the set of curves of type γ0 and of at most length L is asymptotic to L 2 times a constant. 1.Throughout this paper we let Σ be a complete hyperbolic surface of finite area, with genus g and r punctures, and distinct from a thrice punctured s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
53
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 37 publications
(57 citation statements)
references
References 21 publications
3
53
0
1
Order By: Relevance
“…More recently, the number of simple closed geodesics of length ≤ L was shown to be asymptotic to c X · L 6g−6 [Mir08], where c X is a constant depending only on X. Similar results are known to hold for the number of curves up to a given length in a fixed mapping class group orbit [Mir16,ES16].…”
Section: Introductionmentioning
confidence: 76%
“…More recently, the number of simple closed geodesics of length ≤ L was shown to be asymptotic to c X · L 6g−6 [Mir08], where c X is a constant depending only on X. Similar results are known to hold for the number of curves up to a given length in a fixed mapping class group orbit [Mir16,ES16].…”
Section: Introductionmentioning
confidence: 76%
“…In [Mir16], Mirzakhani showed that the same asymptotic growth holds for the mapping class group orbit of any closed curve, without restrictions on the number of intersections. Erlandsson, Parlier, and Souto, see [ES16], [Erl16], and [EPS16], extended Mirzakhani's results to general length functions of closed curves, not only hyperbolic length, that extend to the space of geodesic currents; see [EU18] for a unified discussion. More recently, Rafi and Souto, see [RS17], proved analogous counting results for mapping class group orbits of arbitrary filling geodesic currents.…”
Section: Introductionmentioning
confidence: 96%
“…Here δ x stands for the Dirac measure centered at x. To see what µ Thu actually has to do with the measures ν L = ν γ 0 L recall first that by [10,Proposition 4.1] we have that the family ν L is precompact and that any limit is a multiple of the Thurston measure. Suppose then that ν Ln converges to C · µ Thu .…”
Section: Currents On Surfacesmentioning
confidence: 99%
“…Corollary 1.3 is due for hyperbolic metrics to Mirzakhani [17], generalizing her work on the growth of simple closed geodesics [16]. For non-positively curved metrics, it is due to Erlandsson-Souto [10]. In fact, the results of these papers are instrumental in the proof of Theorem 1.1.…”
mentioning
confidence: 99%
See 1 more Smart Citation